Development of a new method using narrow band imaging for taste assessment. (5th August 2013) - Shimada, Tetsuaki; Kamada, Hideo; Hoshino, Ryuu; Okamiya, Tomofumi; Takahashi, Katsumasa; Chikamatsu, Kazuaki
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The observation of fungiform papillae is a useful objective taste examination. The purpose of this study is to develop a new method using narrow band imaging for assessment of taste function. Study Design Using a narrow band imaging endoscope, we assessed the number and blood vessel morphology of fungiform papillae and compared with the gustatory threshold by the filter paper disc test. Methods The number of fungiform papillae was counted in 20 mm2, and blood vessels in fungiform papillae were evaluated morphologically by a five‐point scoring system in 11 patients who had undergone middle ear surgery. The filter taste disc test was performed simultaneously to obtain the gustatory threshold and was compared with the number and blood vessel morphology of fungiform papillae. Results Using a narrow band imaging endoscope, we could clearly detect not only fungiform papillae but also blood vessel morphology. There was a significant correlation between the values of the number of papillae and blood vessel morphology. Moreover, these two parameters revealed a significant inverse correlation with gustatory function. As expected, both parameters on the affected side were significant lower than those on the unaffected side in patients. Conclusions The assessment of fungiform papillae using narrow band imaging endoscopy is easy, highly sensitive, and reliable; therefore, it might be useful as an objective examination of taste function. Level of Evidence N/A. Laryngoscope, 123:2405–2410, 2013